ASSESSMENT OF EFFICACY IN APPLICATION OF TOPICAL IMMUNOLOGIC RESPONSE MODIFIER FOR PREVENTION OF INFLUENZA AND ACUTE RESPIRATORY INFECTIONS IN CHILDREN - I.N. Lytkina; V.A. Pisareva; T.N. Ivanenko; I.L. Shakhanina (Union of pediatricians of Russia, 2009)
The purpose of this work was to assess the efficacy of bacterial lysate for prevention of acute respiratory infections. The article provides results of monitoring children in the orphanage who were administered the medication of this group as a prophylactic drug against acute respiratory infections. Children also from orphanages who were not administered the medication were selected as a control group. It was found that out of 80 children who underwent preventive treatment, only 26 children fell ill, while out of 80 children in the control group so did 78 orphans. The results achieved allowed the topical immunologic response modifier to be recommended as a general preventive medication for wide use in children in the period of seasonal respiratory infection incidence rate pickup.Key words: influenza, acute respiratory infections, preventive treatment, children.